UTILIZATION OF ANDROID TECHNOLOGY AS AN ALTERNATIVE MEDIA INFORMATION SYSTEM FOR HYBRID-BASED SCHOOL EXAMS - Sari, Dita Novita; Waziana, Winia; Riyadi, Even (Universitas Islam Negeri Raden Intan Lampung, 2022)
The rapid development of information technology on smartphones supported by Android technology can make it easier for users to access all information anywhere and anytime. Currently, many educational institutions use Android as a learning tool and information media as well as various implementations of online student assessments. One of them is the use of CBT (Computer Based Test) facilities. SMK Ma'arif 1 Sendangagung is located in the countryside far from the city centre or district. Implementing student exams/assessments at these school are still manual using paper which has many shortcomings. For example, the leakage of questions in the preparation of exam questions, duplicating and distributing question texts, cheating during the exam, and needing a lot of time to scan answer sheets, require a lot of money, energy, and time. Therefore, an android-based exam application system is needed to make it easier for teachers and students to carry out school exams and semester assessments in a hybrid manner. This research aims to design an Android-based exam application system to make it easier for teachers and students to take grades on students. The use of this technology also aims to make Ma'arif 1 Sendangagung Vocational School more advanced with the application of Android technology. The stages of the research method are first data collection, second data analysis, third application design, and fourth result report. The results of this study are an Android School Examination Application at Maarif 1 Sendangagung Vocational School. The application was built using Delphi EMBARCADERO, Android SDK (Software Development Kit), Android Developer Tools (ADT), and Android Operating System: Froyo 2.2 with Google API SDK 25.2.5, Java, XML. This School Exam Android application can save time in the process of assessing student exam results and make it easier to check student scores